The North (ṣāpôn) in the Book of Jeremiah - Crouch, Carly L. (Zeitschrift für die alttestamentliche Wissenschaft, 2023)
The »foe from the north« is a well-known trope in the book of Jeremiah. In 1989 David Reimer argued that this enemy should be understood as a nonspecific earthly enemy, with mythical overtones deriving from the location of Yhwh ’s divine abode on Mount Zaphon. Contemporary historiographical debates, together with Otto Eißfeldt’s arguments for an Israelite tradition of a »mythischen Nordberg«, exerted significant influence on Reimer’s discussion. This article examines these presuppositions, reconsiders the evidence, and argues that Jeremiah’s enemy »from the north« is a simple geographical reference to the Babylonian Empire.